2001
DOI: 10.1016/s0375-9601(01)00365-6
|View full text |Cite
|
Sign up to set email alerts
|

Super-integrable Calogero-type systems admit maximal number of Poisson structures

Abstract: We present a general scheme for constructing the Poisson structure of superintegrable dynamical systems of which the rational Calogero-Moser system is the most interesting one. This dynamical system is 2N dimensional with 2N − 1 first integrals and our construction yields 2N − 1 degenerate Poisson tensors that each admit 2(N − 1) Casimirs. Our results are quite generally applicable to all super-integrable systems and form an alternative to the traditional bi-Hamiltonian approach.

Help me understand this report
View preprint versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

2
53
0

Year Published

2004
2004
2021
2021

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 32 publications
(55 citation statements)
references
References 21 publications
2
53
0
Order By: Relevance
“…In this context, our geometric proofs of Jacobi identity and of compatibility condition for alternative Poisson structures are different but validate and, in a sense, are complementary to that of Ref. [9].…”
Section: Introductionsupporting
confidence: 63%
See 2 more Smart Citations
“…In this context, our geometric proofs of Jacobi identity and of compatibility condition for alternative Poisson structures are different but validate and, in a sense, are complementary to that of Ref. [9].…”
Section: Introductionsupporting
confidence: 63%
“…The Calogero-Moser system is one of the four nD systems which are known to be maximally superintegrable for any finite integer n [9,14,16]. The other three systems are the Kepler-Coulomb problem, harmonic oscillator with rational frequency ratios, and Winternitz system.…”
Section: Applications a Calogero-moser Systemmentioning
confidence: 99%
See 1 more Smart Citation
“…Among the notable examples are the SU (n) isotropic harmonic oscillator and the SO(4) Kepler problem. Most recently Gonera and Nutku [22] showed that the Nambu structure can be extracted also from the rational Calogero-Moser system [23].…”
Section: P Guhamentioning
confidence: 99%
“…Certain electrodynamic [5,[11][12][13][14][15] and biochemical [16,17] problems have been re-formulated using the multi-Hamiltonian approach of Nambu mechanics. Multi-Hamiltonian oscillators generalizing the harmonic oscillator [18,19], chiral models [8] and the Calogero-Moser system [20,21] have been studied in the context of Nambu mechanics. While one key benefit of Nambu mechanics is that it provides us with a principled way to construct evolution equations from invariants of motion, this benefit also limits the applicability of Nambu's multi-Hamiltonian approach to systems that features such invariants.…”
Section: Introductionmentioning
confidence: 99%